Expression and prognostic significance of human epidermal growth factor receptors 1, 2 and 3 in oesophageal and gastric adenocarcinomas preneoadjuvant and postneoadjuvant treatment. Issue 5 (14th November 2017) - Hedner, Charlotta; Borg, David; Nodin, Björn; Karnevi, Emelie; Jirström, Karin; Eberhard, Jakob
Abstract : Aims: Neoadjuvant treatment has now become the standard of care for oesophageal and gastric cancer. The aim of this study was to investigate the influence of neoadjuvant therapy on the expression of human epidermal growth factor receptor 1 (HER1/EGFR), HER2 and HER3, in oesophageal and gastric adenocarcinoma. Methods: Immunohistochemical expression of EGFR, HER2 and HER3 was examined and compared in pretreatment biopsies, post-treatment surgical resection specimens and metastases in a retrospective cohort of 166 patients with adenocarcinoma of the oesophagus or stomach. The relationship between expression of the investigative markers and histopathological response to neoadjuvant treatment, overall survival (OS) and recurrence free survival (RFS) was analysed. Results: Conversion of protein expression between pretreatment biopsy and post-treatment surgical resection was seen in 4.6% of the cases for EGFR, 5.9% for HER2% and 19.4% for HER3. Histopathological response to neoadjuvant treatment was significantly and stepwise associated with OS and RFS . High HER3 protein expression in post-treatment surgical resection specimens was significantly associated with a prolonged OS in univariable analysis (HR=0.39; 95% CI 0.17 to 0.93), but did not remain significant in multivariable analysis. Expression of EGFR and HER2 in post-treatment surgical resection specimens was not prognostic. No correlation between pretreatment HER-protein expression and histopathological response was seen. Conclusions: The results from this study underscore the need for further studies on the influence of neoadjuvant treatment on biomarker expression, as this may influence treatment strategy as well as prognosis. Histopathological response is validated as a useful prognostic factor.